2016
DOI: 10.4103/0972-9941.178513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low and standard intra-abdominal pressure on systemic inflammation and immune response in laparoscopic adrenalectomy: A prospective randomised study

Abstract: BACKGROUND:The advantages of laparoscopic adrenalectomy (LA) over open adrenalectomy are undeniable. Nevertheless, carbon dioxide (CO2) pneumoperitoneum may have an unfavourable effect on the local immune response. The aim of this study was to compare changes in the systemic inflammation and immune response in the early post-operative (p.o.) period after LA performed with standard and low-pressure CO2 pneumoperitoneum.MATERIALS AND METHODS:We studied, in a prospective randomised study, 51 patients consecutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 69 publications
3
13
0
Order By: Relevance
“…29 Our study results mirrored another laparoscopy study that found significantly higher IL-1, IL-6, and CRP levels in the standard-pressure pneumoperitoneum group than in the low pressure pneumoperitoneum group. 16 Yap et al found that laparoscopic donor nephrectomy resulted in nearly 50% of their subjects showing an increase in tumor necrosis factor-alpha (TNF-) excretion and urine neutrophil gelatinase-associated lipocalin (NGAL) after donor nephrectomy, and also validated the previously published study demonstrating the animal models of AKI after nephrectomy resulted in the increased TNF-, IL-6, and monocyte chemoattractant protein-1 expression. 30 Another animal study showed extrarenal IL-6 production from the liver after unilateral nephrectomy.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…29 Our study results mirrored another laparoscopy study that found significantly higher IL-1, IL-6, and CRP levels in the standard-pressure pneumoperitoneum group than in the low pressure pneumoperitoneum group. 16 Yap et al found that laparoscopic donor nephrectomy resulted in nearly 50% of their subjects showing an increase in tumor necrosis factor-alpha (TNF-) excretion and urine neutrophil gelatinase-associated lipocalin (NGAL) after donor nephrectomy, and also validated the previously published study demonstrating the animal models of AKI after nephrectomy resulted in the increased TNF-, IL-6, and monocyte chemoattractant protein-1 expression. 30 Another animal study showed extrarenal IL-6 production from the liver after unilateral nephrectomy.…”
Section: Discussionsupporting
confidence: 55%
“…The increased intraabdominal pressure causes mechanical compression of the inferior vena cava, renal vasculature, and parenchyma. 13,14 It stimulates sympathetic activity, which is regulated through CO 2 -mediated baroreceptors, and can lead to renal 15,16,17 Advanced venous congestion and decreased renal blood flow leads to tissue hypoperfusion or ischemia that triggers an inflammatory response. 18 Research on animals showed the pneumoperitoneum pressure of 7,15 In humans, increased intra-abdominal pressure caused hypoperfusion in the abdominal or splanchnic regions with or without hypotension, 13,17 and even a slight increased intraabdominal pressure of 10 mmHg has shown to affect the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…29 Our study results mirrored another laparoscopy study that found significantly higher IL-6 levels in the standard-pressure pneumoperitoneum group than in the low pressure pneumoperitoneum group. 16 Yap et al validated the previously published study demonstrating the animal models of AKI after nephrectomy resulted in the increased IL-6. 30 Another animal study showed extrarenal IL-6 production from the liver after unilateral nephrectomy that suggested the elevated cytokine content may be due to the increasing endogenous production.…”
Section: Discussionmentioning
confidence: 61%
“…13,14 It stimulates sympathetic activity, which is regulated through CO 2 -mediated baroreceptors, and can lead to renal cortical vasoconstriction. 15,16,17 Venous congestion and decreased renal blood flow leads to tissue hypoperfusion that triggers an inflammatory response. 18 Research on animals showed the pneumoperitoneum pressure of 12-18 mmHg resulted in hypoperfusion that induced the release of inflammatory cytokines, neutrophil migration, and renal cell apoptosis in the outer medulla and cortex.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that LPP reduced the adverse effects on cardiopulmonary function without affecting laparoscopic feasibility[ 5 , 8 ]. It has also proved feasible and safe in cholecystectomy[ 5 , 9 ], Nissen fundoplication[ 10 ], hysterectomy[ 11 ], adrenalectomy[ 12 ] and donor nephrectomy[ 13 ]. Abdominal wall lift (AWL) is another alternative technique to SPP which avoids the destructive changes associated with CO 2 absorption and increased intraabdominal pressure.…”
Section: Introductionmentioning
confidence: 99%